Determining Factors Influencing Satisfaction with 'Chinese Landscape Painting Appreciation' in Shaanxi, China - Zhang, Changlin (Scholar: Human Sciences, 2026)
Purpose: This paper investigates the factors influencing the satisfaction of art students at Shangluo University regarding the course "Appreciation of Chinese Landscape Painting," taking art students at Shangluo University as the research subject. The conceptual framework posits that a causal relationship exists between social value, image, artistic creativity, and satisfaction. Research Design, Data, and Methods: The quantitative non-probabilistic sampling approach was employed to assess the satisfaction of 148 third-year fine arts students at Shangluo University with this course through questionnaires, encompassing the reliability test (IOC) of the questionnaire, IDI pretest, intervention activity, and IDI posttest. In the post-IDI phase, 30 students were again surveyed and t-tested to complete the post-test. Data analysis was carried out on all variables. Results: Demonstrate that the course "Appreciation of Chinese Landscape Painting" substantially impacts students' satisfaction regarding social value, image, and artistic creativity. Conclusions: The data analysis substantiates the three hypotheses proposed in this study. It also indicates that the objective of this study has been attained. Therefore, in course construction and teaching reform, particular attention should be paid to minimizing the influence of these aspects on students' satisfaction and providing higher-quality course materials to optimize the quality of the course reform.